Pengaruh Pembelajaran Kooperatif Tipe Student Team Achievement Division (STAD) untuk Meningkatkan Hasil Belajar Mahasiswa PGSD Pada Mata Kuliah Konsep Dasar IPA di Universitas PGRI Palembang - Syaflin, Sylvia Lara (SCHOLASTICA JOURNAL : JURNAL PENDIDIKAN SEKOLAH DASAR DAN PENDIDIKAN DASAR (Kajian Teori dan Hasil Penelitian), 2018)
ABSTRACTThis study aims to determine the effect of Student Team Achievement Division (STAD) type of cooperative learning model on learning outcomes in the Basic Science Concept subject in PGSD Students of Palembang PGRI University. The research method used is Quasi-Experimental Research with a research design that is one group pretest-posttest design. The sample in this study was taken using purposive samplingtechnique, so that the 2E class was obtained as the experimental class and 2G class as the control class. The results of this study indicate the average value of student learning outcomes in the STAD class on material magnitude, unit, and measurement for the initial test of 25.97 and the final test 81.44, while in the conventional class for the initial test of 28.70 and the final test 69.74. The results of the t-test indicate thatthe value of t count is greater than t table. Based on the results of the study showed that the application of the Student Team Achievement Division (STAD) cooperative learning model had an influence on the learning outcomes of plant tissue material at PGSD Students of Palembang PGRI University.Keywords: Student Team Achievement Division (STAD) cooperative learning model, learning outcomes.